Specific Primer Designing for Quantitative PCR (qPCR) of Entomopathogenic Fungi Isaria fumosorosea from Soil Samples - Saragih, Syaiful Amri; Takemoto, Shuhei; Sato, Hiroaki; Kamata, Naoto (Jurnal Perlindungan Tanaman Indonesia, 2023)
Entomopathogenic fungi are important component for regulation of pests in ecosystem. Isaria fumosorosea, as one of the entomopathogenic fungi, was reported to successfully controlled the outbreaks of forest defoliators attacked larch (Larix kaempferi) plantation in Furano, Japan and beech (Fagus crenata) forest in Hachimantai, Japan. Instead of semi-cultured method, in this paper, a culture-independent method based on DNA using qPCR was developed for specific detection and quantification of I. fumosorosea directly from soil DNA extract using specific primer. The primer IFU5821F/IFU6061R was designed and found to be the best primer pair for I. fumosorosea. Standard soil DNA was obtained with strong relationship and good fitting with five levels (R2= 0.989, E = 0.58). I. fumosorosea could not be detected from all soil samples which was possibility caused by low density of the fungi. The qPCR was likely a rapid and specific method to detect the fungus from soil.